Fulfillment of Protection Aspects of Buyers with Good Intention for The Dispute of Sale and Purchase of Girik Land where Revocation of Certificate of No Dispute on Land: Study of Supreme Court Decision Number 470K/PDT/2020 - Syahira Ridma Adani; Fransiscus Xaverius Arsin (IHSA Institute, 2022)
In an agreement, good faith plays an important role, because with the good faith shown by the parties in making an agreement, the parties will feel protected. Legal protection for land buyers who have good intentions means that legal protection arises when the buyers themselves transact in good faith. As proof of land ownership, girik cannot be separated from the object of study by a good-intentioned buyer who can also be a party to the sale and purchase transaction of girik land. Buyers and sellers need to pay attention to various conditions for transferring land rights to girik land objects. This also includes paying attention to the conditions both required by the parties themselves as treaty makers and by the state through positive agrarian law regulations applicable at the time of signing the agreement. The analysis in question is presented in this study in order to get a general idea regarding the fulfillment of the protection aspects of buyers who have good intentions for disputes over the sale and purchase of girik land where the certificate of no land dispute has been retracted. This analysis will also use Supreme Court Decision Number 470 K/Pdt/2020 as a case study.